Patients and performative identities at the intersection of the Mesopotamian technical disciplines and their clients - Johnson, Justin Cale, 1971- (Eisenbrauns, 2020)
"A collection of essays investigating how Mesopotamian technical specialists interacted with their clients and in doing so forged their social and professional identities"-- Provided by publisher.
Keywords: Professions -- Iraq -- History -- To 1500.; Iraq -- Intellectual life.; Iraq -- Civilization -- To 634.; Irak -- Civilisation -- Jusqu'à 634.; Civilization; Intellectual life; Professions; Iraq; Civilisation -- Irak -- Jusqu'à 634.; Civilisation assyro-babylonienne -- Aspect economique.; Conditions economiques -- Mesopotamie -- Antiquite.; Professions -- Mesopotamie -- Antiquite.; To 1500; History